"Help Yourself!" What Can Toddlers' Helping Failures Tell Us About the Development of Prosocial Behavior?. (26th May 2017) - Waugh, Whitney E.; Brownell, Celia A.
Abstract : Prosocial behavior emerges in the second year of life, yet it is typical for children in this period not to share, comfort, or help. We compared toddlers (18, 30 months) who helped with those who did not help on two tasks (instrumental helping; empathic helping). More than half of children failed to help on one or both tasks. Nonhelpers engaged in more hypothesis testing on the instrumental helping task, but more security‐seeking, wariness, and playing on the empathic helping task. Across tasks, children who tended to engage in nonhelping behaviors associated with negative emotional arousal also tended to seek comfort from a parent. In contrast, children who tended to play instead of helping were less likely to exhibit negative emotional arousal or hypothesis testing, suggesting a focus on their own interests. Parents of 18‐month‐old nonhelpers on the instrumental task were less engaged in socializing prosocial behavior in their toddlers than were the parents of helpers. On the empathic helping task, 18‐month‐old nonhelpers had less mature self‐other understanding than did helpers. By examining how the predominant reasons for failing to help vary with age and task, we gain a fuller perspective on the factors involved in the early development of prosocial behavior.